Propuesta de mejora bajo los lineamientos Lean Manufacturing para el proceso productivo de la empresa J&K - Rosales Díaz, Gabriel Eduardo; Hernández Pedrozo, Rafael David (Universidad Antonio Nariño, 2021)
Organizations must guarantee their productivity as the main strategy for competitiveness and sustainability. Given the importance of this premise, organizational and engineering sciences have studied and designed different methodologies that adjust to different business models, including those of manufacturing and industrial companies. One of these companies is the company J&K, which is a productive unit of different metal-mechanical products such as home, business and industrial solutions. This company has been presenting a very standard productivity, these due to different factors that generate higher cost in the production process, therefore, this project presents a proposal based on Lean Manufacturing for the company, this is initially a diagnosis of the state of the company, then lean techniques are identified to help transform the reality of the company without this means a large investment for the same, it presents new plant layout and production process and establishes the financial impact that the proposal can generate in the company. Through direct observation and taking into account the fundamentals of process characterization and time studies, waste and new opportunities for the company are established.